Perancangan Poros, Puli dan Sabuk-V Pada Mesin Cuci Samsung Diamond Drum WA80V4 - Richard Julianno Soeganda; Reza Setiawan; Ratna Dewi Anjani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Shafts, pulleys and belts are one component of a washing machine that are no less important than other components. These components function to continue the rotation of the motor to the washing machine tube that will be driven. This study aims to redesign and analyze the three components. The method used is an experimental method with qualitative and quantitative analysis. The results of the analysis show that the diameter of the drive shaft is 8mm with the type of material in the form of carbon steel, the diameter of the drive and driven pulley is 71 mm and 135.8 mm and the material for the cast iron pulley and the type of v-belt used is type A.